Developing Bedrocks Management Concepts in the Period of Capitalism Formation (brief review of scientific papers) - S. A. Bratchenko (Управленческие науки, 2018)
Subject. Management as a science has not arisen from scratch. Management history is an integral part of human history and totals thousands of years. Reasonably a surge of interest to administration issues occurred after bourgeois and industrial revolutions alongside with the class of capitalists was developing. Since their earnings directly depend on how they administer their property. The subject of this work is the economists’ views of that time on the problems of enterprise management. Purpose. The purpose of the article is twofold. 1. To find out what the economists of the 18th and 19th centuries thought of running the enterprise, what problems they considered relevant. 2. The overwhelming majority of management textbooks rightfully begin with the presentation of concept and achievements of management scientific school. However, many thoughts and ideas of managing the enterprise effectively were formulated much earlier. Therefore, the second goal of the article is to reveal the contribution of scientists of this period to the later science of management. The management thought topics of the capitalism development period have not been fully presented in the Russian science. The given article does not claim to cover the topic in detail, but is an attempt to contribute to filling this scientific gap.Methodology. Examination and analysis of the economic works of 18th and 19th centuries (by both scientists and practitioners), their views systematization on the problems of enterprise management.Results. In the result of the analysis it has been shown that the scientists and practitioners of that period realized the necessity of planning, organizing, accounting and controlling at an enterprise. They considered the issues of human resources management and motivation, social responsibility of business. The concept of entrepreneur and the entrepreneur professional capacities were widely discussed.Conclusions. The foundations of management as a science were laid due to consideration of a wide range of issues by scientists and entrepreneurs of that period. These investigations became a basis for further development of management (both as a social phenomenon and as a science) in the 20th century.